The use of antidepressants in adolescence and their self-medication (Research, Society and Development, 2021)
Introduction: Over the years, depression has been growing more and more in society and affecting age groups such as adolescents, adults, and the elderly. Depression is a psychiatric disorder that can cause several unwanted symptoms. Its treatment is carried out by means of antidepressants, and self-medication can cause serious problems to the user, such as dependence and unwanted effects. Objective: To verify the main characteristics of the use of antidepressants in adolescence and its self-medication as well as one of the main reasons that cause depression in adolescence. Methodology: The data were collected from the scientific online databases EBSCO, Science Direct and SCIELO. The descriptors used were: Self-medication, Self-medication in adolescence, Depression and consequence of antidepressants. As inclusion criteria, 30 articles published between the years 2010 and 2021 were selected. The articles that did not meet the inclusion criteria were not used for the construction of the article. Conclusion: This study is important to identify the antidepressants most commonly used by adolescents and the risks caused by the practice of self-medication. During the research, it was possible to observe that the main drugs prescribed for adolescents with depression are Fluoxetine and then the medications amitriptyline, venlafaxine, paroxetine, sertraline and citalopram, thus to encourage more research on the subject, since the subject is not properly broad, and depression is a psychopathology not so easy to be diagnosed and so relevant in society today.